Improving compostable plastic disposal: An application of the Behaviour Change Wheel intervention development method - Allison, Ayşe Lisa; Purkiss, Danielle; Lorencatto, Fabiana; Miodownik, Mark; Michie, Susan (Frontiers in Sustainability, 2022)
Compostable plastics have great potential environmental benefits, however, the damage caused by incorrect waste management offsets them. This study aims to develop a behaviour change intervention aimed at improving disposal of compostable plastics. We illustrate application of the Behaviour Change Wheel framework to design an intervention in this context. First, the target behaviour was understood by specifying it and identifying potential behavioural influences. Second, behavioural influences were systematically linked to potential intervention strategies and refined by evaluating the likely affordability, practicability, effectiveness, acceptability, equity and potential for side-effects (APEASE criteria) in a UK implementation context. Finally, intervention content and implementation options were selected by systematically selecting specific Behaviour Change Techniques and refining them by evaluating them against APEASE criteria. The target behaviour was identified as UK citizens disposing of compostable plastic waste in the food waste bin meant for collection by local authorities. Influences on compostable plastic disposal were identified as ‘psychological capability’ (i.e., attention and knowledge), ‘reflective motivation’ (i.e., beliefs around environmental impact of compostable plastics) and ‘physical opportunity’ (i.e., access to appropriate waste management). ‘Education’ and ‘environmental restructuring’ were the intervention types selected. ‘Communications/marketing’, ‘guidelines’ and ‘restructuring the physical and social environment’ were the policy options selected. Selected behaviour change techniques were: instruction on how to perform the behaviour, prompts/cues, adding objects to the environment and restructuring the physical environment. The resulting intervention is a disposal instruction label for compostable plastics, comprising of instructions and a logo. The next step is user testing the developed disposal instruction labels in terms of their effect on promoting the desired disposal behaviour. Our work has key applied and theoretical implications. We have designed an intervention that, when evaluated, has the potential to provide important answers relating to how best to get citizens to dispose of compostable plastic waste appropriately. This, in turn, has key policy implications for product and package labelling. Openly documenting the intervention development process not only promotes a systematic, comprehensive and transparent approach to intervention design but it also provides an adaptable template and model for other researchers.